Annexin Expression in Cholangiocarcinoma, and Metastatic Pancreatic Ductal Adenocarcinoma "Is it be Helpful for Differential Diagnosis of These Tumors in the Liver?" - Bita Geramizadeh; Mahsa Sehat; Azam Mehrmozayan; Alireza Shojazadeh (Iranian Society of Pathology, 2021)
Background & Objective: Differential diagnosis between cholangiocarcinoma (CCA) and metastatic pancreatic ductal adenocarcinoma (PDA) in the liver is difficult and so far, no specific immunohistochemical marker is reported to differentiate these two tumors. Considering the existing literature, the level of expression of Annexins (Annexin A1, 10 and 13) have been studied for differential diagnosis between these two tumors by molecular methods and promising results have been reported. Therefore, in this study, we tried to investigate the immunohistochemical value of these three Annexins for the differential diagnosis of CCA and PDA in the liver.Methods: The articles that reported the research subject in 10 years (2009-2019), including 45 cases of CCA and 50 cases of metastatic PDA in the liver were evaluated considering the presence or absence of AnnexinA1 (ANXA1), Annexin A10 (ANXA10) and Annexin A13 (ANXA13) expression by immunohistochemistry, were investigated.Results & Conclusion: This study showed, ANXA1 was positive both in PDA and CCA, ANXA10 was positive in ~60% of PDA cases and ~40% of CCA cases, and ANXA13 was mostly negative in both groups. The best sensitivity was found in cytoplasmic and nuclear ANXA1 (80% and 84%, respectively) to distinguish PDA from CCA and vice versa. The best specificity was observed in ANXA10 and ANXA13 to distinguish PDA from CCA. Also, ANXA13 had the best specificity to distinguish CCA from PDA. Our investigations showed that, ANXA1 probably can classify positive cases correctly, but it cannot discriminate PDA from CCA. ANXA10 had fair sensitivity and specificity to discriminate PDA from CCA. ANXA13 apparently had a high specificity that can help to narrow-down the differential diagnoses.